1987
DOI: 10.1111/j.1432-1033.1987.tb13611.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of the K+-channel-associated apamin-binding molecule in smooth muscle, liver and heart membranes

Abstract: High-affinity binding sites for m~no ['~~I]iodoapamin were detected in membranes (Kd = 59 pM, B,,, = 24 fmol/mg protein) and cultured cells (& = 69 pM, B,,, = 2.8 fmol/mg protein) from rat heart and in membranes from guinea-pig ileum (& = 67 pM, B, , , = 42 fmol/mg protein) and liver (Kd = 15 pM, B,,, = 43 fmol/ mg protein). Binding was stimulated by K t ions = 0.3-0.5 mM). Covalent labeling with arylazide ['251]iodoapamin derivatives showed that smooth muscle, liver and heart binding molecules are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(9 reference statements)
1
6
1
Order By: Relevance
“…1A) and the cross-linking experiments (Fig. 1B), our results do not support the suggestion, by others, that the smaller protein species ("p50 doublet" in this work) is also capable of binding apamin (Seagar et al, 1986;Marqueze et al, 1987).…”
Section: Resultscontrasting
confidence: 55%
“…1A) and the cross-linking experiments (Fig. 1B), our results do not support the suggestion, by others, that the smaller protein species ("p50 doublet" in this work) is also capable of binding apamin (Seagar et al, 1986;Marqueze et al, 1987).…”
Section: Resultscontrasting
confidence: 55%
“…In concentrations of 10-50 nM, apamin blocks the 42 K ϩ efflux and K ϩ conductance increase caused by adrenergic stimulation of isolated guinea pig hepatocytes (3,4) and prevents the increase in K ϩ conductance caused by metabolic stress in liver and biliary cell lines (22,23). Moreover, there appear to be ϳ1,700 apamin binding sites per liver cell, although more than one target protein may be involved (7,13). On the basis of these observations, the purpose of these studies was to assess whether apamin-sensitive SK Ca channels are expressed in liver epithelia and to evaluate whether they contribute to cell volume regulation and modulation of volume-sensitive liver functions.…”
mentioning
confidence: 99%
“…Our tentative conclusions are however in keeping with other evidence that suggests that the SKCa channels are heterogeneous. Photoaffinity labelling and chemical crosslinking studies with [1251]-apamin have already identified a number of apamin binding polypeptides (Schmid-Antomarchi et al, 1984;Marqueze et al, 1987;Auguste et al, 1989), suggesting the SKCa channel is composed of several subunits. While all the cell types studied have yielded a protein of approximately 30 kDa, its size has been reported to range from 25 to 33 kDa, depending on the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In another approach, some progress has been made towards the biochemical characterization of apamin binding proteins-presumed to form part of the SKca channel (Schmid-Antomarchi et al, 1984; ' Author for correspondence. Marqueze et al, 1987;Auguste et al, 1989). An important recent study by Wadsworth et al (1994) has provided evidence that these proteins vary between species and in the same work it was shown that the neuromuscular blocking agent, gallamine, is less effective in displacing labelled apamin from its binding site in rat brain than in rabbit and guinea-pig liver.…”
Section: Introductionmentioning
confidence: 99%